2014
DOI: 10.3917/spub.137.0089
|View full text |Cite
|
Sign up to set email alerts
|

Les difficultés d'accès aux soins de santé des indigents vivant dans des ménages non pauvres

Abstract: The community perceives poverty in terms other simply economic aspects. The social dimension of poverty (including the inability to fully participate in community life) has a major impact on the choice of the CVS, leading to the selection of indigents from households that appear to have a high economic level. This community process which takes into account contextual factors, identified these people who do not necessarily have access to the household resources for health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…A number of studies have found an association between spatial inequalities in access to care and spatial heterogeneity of malaria incidence [42,43]. Yet, contrary to what has been reported elsewhere [44], we failed to found a correlation between the number of malaria cases and the Euclidean distance between villages and their corresponding HC.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of studies have found an association between spatial inequalities in access to care and spatial heterogeneity of malaria incidence [42,43]. Yet, contrary to what has been reported elsewhere [44], we failed to found a correlation between the number of malaria cases and the Euclidean distance between villages and their corresponding HC.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of studies have found an association between spatial inequalities in access to care and spatial heterogeneity of malaria incidence 34 , 35 . Yet, contrary to what has been reported elsewhere 36 , we failed to found a correlation between the number of malaria cases and the Euclidean distance between villages and their corresponding HC.…”
Section: Discussionmentioning
confidence: 99%
“…Given difficult living conditions and rapid social changes, it appears elders are becoming more numerous and more dependent on their children, who unfortunately are often unable to take care of their aging parents [ 42 ]. Other studies in Burkina Faso have identified elders as a population incurring several risks, such as not having their basic needs fulfilled [ 43 ], being vulnerable and needing particular help and support [ 13 , 22 ], experiencing psychological distress and depressive symptoms [ 43 ], and being marginalized due to their increasing psychological distress and diminished functioning, which can be related to shame for family members [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanama and Frongillo [ 34 ] found, in a rural setting in Burkina Faso, that food insecurity was an important vulnerability factor associated with anxious, depressive, and somatic symptoms. Duthé and colleagues also found that poor health status predicted the risk of developing depressive symptoms [ 35 ], and a qualitative study conducted with indigents and their relatives showed that poor health status was an indicator of extreme vulnerability, even among the least poor households identified as worst-off in rural settings [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation